Hubungan Faktor Lingkungan Permukiman Lahan Basah terhadap Kejadian Gangguan Kulit di Kecamatan Kertapati - Putri, Dini Arista; Widya Ayu Pratiningsih; Trisnaini, Inoy; Girsang, Fetri Vera; Hoirunnisa, Najma; Nurhayati; Fitriani, Revia Najwa; Oktaviandi, Shanti; Aryani, Titin Dwi (LPPM Hang Tuah Pekanbaru, 2025)
Skin disorders are common health problems, particularly among communities living in environments with poor sanitation such as wetland settlements. Palembang City Health Office data in 2023 shows skin diseases ranked seventh with 21,271 cases, while in Kertapati District, scabies and pyoderma prevalence among elementary school children reaches over 60%. This study aims to analyze the relationship between environmental factors in settlements—including occupancy density, housing physical conditions, waste management, water quality, and flood risk—and the incidence of skin disorders in Kertapati District, Palembang City. A quantitative study with a cross-sectional design and purposive sampling technique was conducted involving 106 respondents residing in Kemas Rindo and Ogan Baru subdistricts. Data were collected through structured questionnaires and analyzed using chi-square tests and multiple logistic regression. Bivariate analysis showed significant associations between wall type (p=0.032) and floor type (p=0.037) with the incidence of skin disorders. Multivariate analysis identified floor type as the most dominant factor (p=0.007; Exp(B)=4.718), followed by ceiling type (p=0.010; Exp(B)=0.262). The findings indicate that environmental factors, particularly floor and ceiling types, contribute to the risk of skin disorders. Improving the quality of housing infrastructure is necessary to reduce skin disorder cases in wetland areas.